Impact of Implementing Education and Training Programs for Competency Development of Civil Servants - Elfiyanto Zega; Syah Abadi Mendrofa (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study intends to: 1) take a deep analysis of the effectiveness of the education and training programs implemented by BKPSDM Gunungsitoli to improve employee knowledge and skills, 2) discover the obstacles encountered in the implementation of education and training programs at BKPSDM Gunungsitoli and the solutions to overcome these obstacles to increase program effectiveness. Using a qualitative method, the data are gathered through interviews with employees, participatory observation, and documentary analysis regarding the education and training programs administered by BKPSDM. A purposive sampling technique is applied in this study. Data sources comprise two primary categories, namely primary and secondary data sources. The investigation regarding the implementation of education and training programs at BKPSDM Gunungsitoli, as well as the impact of their implementation on developing the competency of civil servants, summarize that: 1) The education and training programs implemented by BKPSDM Gunungsitoli significantly and positively impact the development of civil servant competency. Through this program, employees can improve knowledge, skills, and attitudes relevant to the demands of their position; 2) Despite the positive impact, the implementation of education and training programs at BKPSDM Gunungsitoli still encounters various challenges. To improve the effectiveness of this program, improving the curriculum evaluation, integrating with operational needs, and increasing the availability of infrastructure and involvement of work units are crucial.